Effectiveness and duration of two-arch fixed appliance treatment - Chew Ming Tak; Sandham Andrew (Sciendo, 2000)
The aims of this study were to determine the effectiveness and duration of single-phase two-arch fixed appliance treatment and to evaluate factors that may influence these two variables. Data were collected from 177 consecutively completed cases at the Orthodontic Department, Government Dental Clinic, Singapore, during a three-month period. Pre-treatment and post-treatment models were assessed using the Peer Assessment Rating (PAR) index. The result showed that two-arch fixed appliance treatment reduced the malocclusions on average by 77.80 per cent over a period of 25 months. Multiple regression techniques revealed that 22 per cent of the variability in treatment effectiveness could be explained by the pre-treatment PAR score, the age at the start of treatment, the frequency of office visits and whether or not the treatment involved extractions. The variation in treatment duration was due to the frequency of office visits, the pre-treatment PAR score and whether or not the treatment involved extractions or headgear.